An integrated learning scheme for community practitioners involved in the care of children and young people. (November 2017) - Alexander, Emma C; de Silva, Debra; Clarke, Rachel; Peachey, Meradin; Manikam, Logan
Abstract: Background: Many health, education, and voluntary groups provide services for children and their families, but this care tends not to be integrated. In a deprived borough of London, we aimed to test whether providing short training and networking sessions would improve knowledge and referrals between services supporting children. Methods: This uncontrolled longitudinal study was completed as a service evaluation. Three sets of workshops were offered in each of four geographical localities from December, 2016, to February, 2017. Relevant local organisations were invited to send attendees to all sessions. The sessions involved case discussions, team-working exercises, and presentations from teams such as local health visitors and child and adolescent mental health services. Mixed methods were used to assess impacts including preworkshop and postworkshop surveys with a Likert scale for statements such as "I know a lot about local health services". These covered knowledge of health, education, social care, and voluntary sectors; confidence in navigating local services; and communication between different services. Analysis of quantitative data used unpaired t tests since questionnaires were anonymised. Other methods included structured telephone interviews and a 1 month follow-up survey. Findings: There were 302 attendances from 202 unique individuals. Attendees came from 22 local services from the health (n=99), education (145), social care (39), and voluntary (19) sectors. The preworkshop and postworkshop surveys (completed across 254 [84%] and 220 [73%] of attendances, respectively) demonstrated significant increases in self-assessed knowledge of health, education, social care, and voluntary services, and of confidence in intersector working (all p<0·0001). However, self-assessed knowledge and confidence had decreased by 1 month follow-up (completed by n=65). Respondents to the follow-up survey who attended all workshops (n=24) had higher scores than those who did not, regarding knowledge of voluntary services (p=0·049) and recent collaboration (p=0·014). Telephone interviewees (n=30) suggested that networking was helpful. Interpretation: We found that participants had transient increases in self-assessed knowledge and confidence in intersector working. The findings imply that professionals may find such integrated schemes useful, but further development is required to embed knowledge and connections long term. Further research should assess the impact of such schemes on patients or clients. Funding: This study was funded by Newham Together, the Newham Community Education Provider Network, hosted by NHS Newham Clinical Commissioning Group. LM is funded by a National Institute for Health Research doctoral research fellowship (DRF-2014-07-005).